How students translate bilingual picture book using multimodality: Translation process phenomenology - Wijaya, Ikha Adhi; Nugroho, Andy Bayu; Alzuhdy, Yosa Abduh; Jupply, Donald (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2023)
The multi-modal translation process greatly influences the results of the translation of children's picture storybooks produced by Yogyakarta State University students. Bildung from the translator and the method used is a guarantee to produce a quality translation. This research tries to reveal the translation process of children's picture stories from genetic, generic, and affective aspects. The data were analyzed using the distribution and referential method. Through the SFL and VG (multi-modal) approaches, the researcher reveals the translation process carried out by students of English Literature at Yogyakarta State University. The research results show that genetic aspects obtained from interviews and questionnaires are positively correlated with affective aspects. The positive results of the synthesis of both are also confirmed by positive patterns in the generic aspect. This is proven through the intercorrelation of text and images which complement each other in presenting an interpretation for a comprehensive reader. Based on the intercorrelation of these three aspects, it can be concluded that based on this phenomenon, translators in the translation process use multimodality theory to present appropriate translations with good translation quality.